AKSELERASI PENGEMBANGAN DESTINASI WISATA DANAU TOBA (Studi Realisasi Prinsip Good Governance Pada Badan Pelaksana Otorita Danau Toba) - Nurul Annisa Wulandari; Dede Sri Kartini; Neneng Yani Yuningsih (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
This research is motivated by Lake Toba tourism which has not been managed optimally, resulting in low interest in tourist visits. In addition to overlapping central and regional government authority arrangements, this condition is exacerbated by the lack of public understanding regarding tourism, the lack of information disclosure, and the lack of involvement of indigenous peoples which have implications for the rise of community land acquisition conflicts. The purpose of this study is to explain how BPODT develops Lake Toba tourist destinations based on the principles of good governance proposed by Sedarmayanti (2007) based on aspects of transparency, accountability, and participation. The research is qualitative, primary data obtained through observation and interviews, data analysis and validation using triangulation. The results show that the development of Lake Toba tourism objects by BPODT is still not optimal, it can be seen that there is a lack of openness, information, and coordination. Based on the accountability aspect, BPODT is trying its best to make the Lake Toba tourist area a world-class tourism area that is superior and supported by adequate infrastructure. As well as implementing ecosystem maintenance policies through the prevention and management of the Lake Toba tourist attraction area. Regarding the participation of BPODT and stakeholders, it is currently running, although there are still land acquisition conflicts. As well as implementing ecosystem maintenance policies through the prevention and management of the Lake Toba tourist attraction area. Regarding the participation of BPODT and stakeholders, it is currently running, although there are still land acquisition conflicts. As well as implementing ecosystem maintenance policies through the prevention and management of the Lake Toba tourist attraction area. Regarding the participation of BPODT and stakeholders, it is currently running, although there are still land acquisition conflicts.